E-Budgeting Applications Design and Analysis using an Object-Oriented Approach for The Aircraft Service Company - Rangga Sidik; Indra Septian Heru; Syahrul Mauluddin (The IJICS (International Journal of Informatics and Computer Science), 2021)
This study aims to analyze and design an e-budgeting application at an aircraft service company in Indonesia. This aircraft service company has a budget management division plan in preparing budget planning and monitoring budgets. In its implementation, the current system procedure has experienced several errors including 1) slow data processing; 2) budget monitoring is not running according to procedure; and 3) the system is not integrated with one another. The method used in this research is a case study while the data were collected through interviews and direct observation. The analysis and design used object-oriented approach with the Unified Modeling Language as a tool. In addition, the system development model used in designing the system is prototype. The result of this research is an e-budgeting application which can facilitate the program management division of aircraft service companies in budget planning and monitoring of budgets effectively and efficiently. The proposed e-budgeting has been designed, built, and tested using the black box testing method. Every function that is part of the requirements for the budget management system has been fulfilled 100%. The activity flow of the budget submission process to validation and confirmation can be carried out properly. The results show that the proposed E-budgeting application gives an alternative solution to solve their known issues compared to the budgeting existing system before